Advancements in Insect Science: Agricultural, Health, and Biotechnological Applications for Sustainability - Dr. V. Basil Hans (International Journal of Insects, 2025)
Insect research is very important for solving problems in agriculture, health, industry, and protecting the environment. This article talks about the many uses of entomology and how new study on insects helps with pest control, pollination, disease vector control, and the creation of bioinspired technologies. There is a lot of talk about integrated pest management (IPM) tactics, using insects in forensic investigations, and the new sector of producing insect- based protein for food and feed. The report also talks about how molecular technologies and genetic engineering are helping us learn more about insect biology and come up with new ways to lessen the effects of invasive species and diseases that are spread by vectors. Insect science is a potent instrument for enhancing ecological resilience, food security, and human health when scientists from different fields work together.
Keywords: Insect biotechnology; Pollination; Sustainable agriculture; and vector control; pest management